Unveiling new chapters in medullary thyroid carcinoma therapy: advances in molecular genetics and targeted treatment strategies - Huai, Jia-Xuan; Wang, Fang; Zhang, Wen-Hui; Lou, Yan; Wang, Gao-Xiang; Huang, Li-Ji; Sun, Jing; Zhou, Xi-Qiao (Frontiers in Endocrinology, 2024)
Medullary Thyroid Carcinoma (MTC), a neuroendocrine malignancy that arises from the calcitonin-secreting parafollicular C-cells of the thyroid, constitutes a minor yet impactful fraction of thyroid malignancies. Distinguished by its propensity for aggressive growth and a pronounced tendency for metastasis, MTC poses formidable obstacles to the early diagnosis and therapeutic intervention. The molecular genetics of MTC, particularly the role of the RET gene and the RAS gene family, have been extensively studied, offering insights into the pathogenesis of the disease and revealing potential therapeutic targets. This comprehensive review synthesizes the latest advancements in the molecular genetics of MTC, the evolution of precision therapies, and the identification of novel biomarkers. We also discuss the implications of these findings for clinical practice and the future direction of MTC research.